2020
DOI: 10.1007/s00360-020-01266-5
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in night-time metabolic rate and body temperature in a small passerine

Abstract: Spending the winter in northern climes with short days and cold ambient temperatures (T a) can be energetically challenging for small birds that have high metabolic and heat loss rates. Hence, maintaining body temperature (T b) in T a below thermoneutrality can be energetically costly for a small bird. We still know little about how increased heat production below thermoneutrality affects the level at which T b is maintained, and if these patterns are age specific. To test this, we measured subcutaneous body t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Montane taxa showed 1) an increase in the proportion of down, and a small but significant increase in relative feather length, with an increase in elevation and 2) a significant decrease in the proportion of the downy region and relative feather length with an increase in body size. Birds show intraspecific variation in feather structure associated with environmental variables (Andreasson et al 2020), a pattern demonstrated along latitudinal (Broggi et al 2005) and elevational axes (de Zwaan et al 2017). Pap et al (2017Pap et al ( , 2020 in a phylogenetic comparative approach, showed that feather structure variables known to vary within species, also vary across species, in association with environmental temperatures in Eurasian temperate birds.…”
Section: Discussionmentioning
confidence: 99%
“…Montane taxa showed 1) an increase in the proportion of down, and a small but significant increase in relative feather length, with an increase in elevation and 2) a significant decrease in the proportion of the downy region and relative feather length with an increase in body size. Birds show intraspecific variation in feather structure associated with environmental variables (Andreasson et al 2020), a pattern demonstrated along latitudinal (Broggi et al 2005) and elevational axes (de Zwaan et al 2017). Pap et al (2017Pap et al ( , 2020 in a phylogenetic comparative approach, showed that feather structure variables known to vary within species, also vary across species, in association with environmental temperatures in Eurasian temperate birds.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, basal metabolic rate seems to decline with increasing age in birds and mammals (see meta-analysis in Elliott et al, 2015), which may hint to a lower body temperature. Lower body temperature with increasing age has been shown in several studies (see review Kelly, 2006;Andreasson et al, 2020) and such a decrease in body temperature with age may be related to the inability to produce more heat or maintain the heat. For instance, changes in body fat with advancing age might explain lower body temperature in elderly humans in comparison to young (Van Someren et al, 2002;Kenney and Munce, 2003;DeGroot and Kenney, 2007), while in birds subcutaneous fatloss could affect insulation and the capacity to maintain heat.…”
Section: Impaired Thermoregulation With Increasing Age As a Potentialmentioning
confidence: 92%
“…One-two days after capture the birds were implanted with a temperature-sensitive PIT tag (BioTherm13, Biomark, Boise, ID, USA) into the intraperitoneal cavity under local anaesthesia (5% lidocaine) as part of a different study. Eight to 34 h later, the birds were put in a 1 L hermetically sealed glass container ventilated with dry air at 400-500 ml / min (recorded using a FB-8 mass flow meter, Sable Systems, Las Vegas, NV, USA) for measurement of resting metabolic rate (RMR; as oxygen consumption recorded in carbon dioxide-free air using a FC-10 oxygen analyser, Sable Systems) and body temperature (recorded using a custom-built multiplexed antennae system from BioMark) in a climate chamber (Weiss Umwelttechnik C180 [Reiskirchen, Germany]) at thermoneutrality (25 °C; n = 20) [13], during a simulated mild winter night (5 °C: n = 19) and during a simulated very cold winter night (−15 °C; n = 19) for 13-15 h. Four birds were measured each night. Mean RMR was 0.36 ± 0.01 W (mean ± s.e.m.…”
Section: Methodsmentioning
confidence: 99%
“…However, the modest extent of hypothermia means that the little bird in winter can never forego a significant increase in energetically costly heat production to counter winter cold, even when maximally hypothermic (e.g. 15 ).…”
Section: Introductionmentioning
confidence: 99%